14q32 translocations and 13q14 deletions are common cytogenetic abnormalities in POEMS syndrome2. (10th October 2013) - Kang, Wen‐Ying; Shen, Kai‐Ni; Duan, Ming‐Hui; Zhang, Wei; Cao, Xin‐Xin; Zhou, Dao‐Bin; Li, Jian
Abstract Objective POEMS syndrome is a paraneoplastic syndrome characterized by polyneuropathy, organomegaly, endocrinopathy, monoclonal plasma cell (PC) proliferative disease, and skin changes. Although chromosomal aberrations have been found and extensively described for other PC disorders, whether POEMS syndrome shares similar cytogenetic profiles has been rarely reported. In this study, we aimed to clarify the cytogenetic abnormalities of patients with POEMS syndrome in our center. Methods Purified CD138+ PCs from bone marrow samples of twenty patients with POEMS syndrome were studied by interphase fluorescence in situ hybridization (FISH). FISH results were analyzed for an association between cytogenetic changes and clinical features. Results A majority of patients (65%) were found to bear cytogenetic aberrations commonly seen in multiple myeloma. The 14q32 (IGH) translocation was observed in 45% of the cases and included the t(4;14) and t(11;14) translocation (15% and 25% of the cases, respectively). In addition, 25% of the patients had deletions of 13q14 and 20% had an amplification of 1q21. No significant correlation between clinical features with cytogenetic abnormalities was observed, although patients with IGH translocations were more likely to exhibit papilledema (P = 0.018). Conclusion Cytogenetic aberrations in POEMS syndrome were similar to other PC dyscrasias, but at different percentages.